Six-minute walk test in pulmonary arterial hypertension - Demir, Rengin (Anatol J Cardiol, 2015)
Exercise intolerance is the main characteristic of pulmonary arterial hypertension (PAH). The six-minute walk test (6MWT) and cardiopulmonary exercise test are widely used in assessing exercise capacity of PAH patients. Six-minute walk distance (6MWD) has been specified as the main clinical outcome in PAH and has been used as the primary end-point in many studies conducted for new PAH treatments. Using 6MWD as the end-point in clinical studies has many advantages. 6MWT is an inexpensive, easily applicable, and repeatable standardized test that is well-tolerated by PAH patients. Moreover, it is a valid measure of symptomatic improvement. It is correlated with variables of maximal cardiopulmonary exercise test as a measure of submaximal exercise capacity and disease severity markers such as functional class and pulmonary hemodynamics. It is widely used in clinical practice together with other invasive and non-invasive disease markers in assessing disease progression and response to treatment. In addition, it has prognostic importance and is a good prognostic marker. On the other hand, there are limitations to the use of 6MWD as the primary end-point in PAH treatment. It has decreased sensitivity in individuals with less severe disease and high 6MWD at baseline and decreased adequacy in assessing the effects of treatment in patients who are still under PAH treatment. Despite the limitations, 6MWD plays a key role in the evaluation and management of PAH patients.